NITROGEN AND BORON FERTILIZATION ASSOCIATED TO THE INOCULATION WITH Bacillus subtilis IN THE AGRONOMIC PERFORMANCE OF COMMON BEAN - Silva, M. S.; Oliveira, G. R. F.; Bossolani, J. W.; Proença, S. L.; Soares, D. A.; Rocha, E. N.; Teixeira Filho, M. C. M.; Sá, M. E. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The common bean is a grain widely consumed by the Brazilian population, characterized as a source of protein accessible to the population of low economic power. However, Brazilian productivity is incipient due to its local importance. The aim of this experiment was to verify the effect of foliar fertilization with nitrogen and boron, associated or not to inoculation with Bacillus subtilis on the agronomic performance of common bean cv. Formoso. The experiment was carried out in a dystrophic Red Latosol, under no - tillage conditions, in the municipality of Selvíria, Mato Grosso do Sul, Brazil. The experimental design was in randomized blocks, with nine treatments and four replicates. The commercial products used were: Nitrobor® (10.2 g of nitrogen L-1 + 2.04 g of boron L-1) and Panta® (1.0 x 109 f.c. of B. subtilis mL-1). The treatments were established by nine doses of Nitrobor® + Panta® (0 mL ha-1 + 0 mL ha-1; 150 mL ha-1 + 0 mL ha-1; 250 mL ha-1 + 0 mL ha-1; 350 mL ha-1 + 0 mL ha-1; 450 mL ha-1 + 0 mL ha-1; 150 mL ha-1 + 350 mL ha-1; 250 mL ha-1 + 350 mL ha-1; 350 mL ha-1 + 350 and 450 mL ha-1 + 350 mL ha-1). Inoculation with B. subtilis via aerial part, associated or not with foliar fertilization with nitrogen and boron at different doses, does not influence plant height, production components and grain yield of common bean.